2018
DOI: 10.11606/rdg.v0ispe.142698
|View full text |Cite
|
Sign up to set email alerts
|

Características Granulométricas e Morfológicas das Areias de Solos sobre Arenitos e Basaltos em Floraí/PR

Abstract: O artigo aborda as diferenças nas formas de relevo e materiais associados (rochas, solos e depósitos) do setor noroeste do estado do Paraná, região sul do Brasil. Discute, em nível de detalhe, a geometria de uma vertente e as especificidades granulométricas e morfológicas das areias de um solo sobre o arenito da Formação Caiuá (Grupo Bauru), em comparação com outro nos basaltos da Formação Serra Geral (Grupo São Bento), na bacia hidrográfica do Córrego Gurupá. Para tanto, foram realizados procedimentos em gabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…It was not our goal to discuss the soil transformations in the catena. An in-depth discussion about soil development in systems similar to the study area could be found elsewhere (Cunha et al, 1999;Zaparoli and Gasparetto, 2010;Cunha et al, 2016;Barreiros et al, 2018). Overall, Lixisols was highlighted as the most erodible soil along the catena (Cunha et al, 1999(Cunha et al, , 2016Merten et al, 2016).…”
Section: Discussionmentioning
confidence: 86%
“…It was not our goal to discuss the soil transformations in the catena. An in-depth discussion about soil development in systems similar to the study area could be found elsewhere (Cunha et al, 1999;Zaparoli and Gasparetto, 2010;Cunha et al, 2016;Barreiros et al, 2018). Overall, Lixisols was highlighted as the most erodible soil along the catena (Cunha et al, 1999(Cunha et al, , 2016Merten et al, 2016).…”
Section: Discussionmentioning
confidence: 86%